2010
DOI: 10.1016/j.ccr.2009.12.047
|View full text |Cite|
|
Sign up to set email alerts
|

An Activated ErbB3/NRG1 Autocrine Loop Supports In Vivo Proliferation in Ovarian Cancer Cells

Abstract: Summary Ovarian cancer is a leading cause of death from gynecologic malignancies. Treatment for advanced-stage disease remains limited and, to date, targeted therapies have been incompletely explored. By systematically suppressing each human tyrosine kinase in ovarian cancer cell lines by RNAi, we found that an autocrine signal-transducing loop involving NRG1 and activated-ErbB3 operates in a subset of primary ovarian cancers and ovarian cancer cell lines. Perturbation of this circuit with ErbB3-directed RNAi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
142
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(144 citation statements)
references
References 42 publications
1
142
0
Order By: Relevance
“…Increasing evidence links HRG/ErbB3 signaling to mammary tumorigenesis and metastasis. In addition, studies have assigned key roles to autocrine HRG-mediated activation of ErbB3/ErbB2 in sustaining tumor growth and conferring resistance to therapeutic agents (15,17,25,26,28,(72)(73)(74). The fact that ErbB3 signals primarily through activation of the PI3K pathway (1,7,8) invariably argues for a prominent role of the receptor in shifting the balance toward enhanced cell survival, invasiveness, and the maintenance of the tumor phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence links HRG/ErbB3 signaling to mammary tumorigenesis and metastasis. In addition, studies have assigned key roles to autocrine HRG-mediated activation of ErbB3/ErbB2 in sustaining tumor growth and conferring resistance to therapeutic agents (15,17,25,26,28,(72)(73)(74). The fact that ErbB3 signals primarily through activation of the PI3K pathway (1,7,8) invariably argues for a prominent role of the receptor in shifting the balance toward enhanced cell survival, invasiveness, and the maintenance of the tumor phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…However, many recent studies showed that this receptor is very important in cancer. ErbB3 has been regarded to cause cell proliferation of cancer cells (Sheng et al 2010), and some ErbB3-targeting drugs are being developed in their clinical phases, such as the ErbB3 antibody MM-121 . Therefore, miR-22 will be a potential therapeutic drug to target ErbB3 for treatment of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…So far, no predominant pathway ('addicting' oncogene) has been shown in ovarian tumors. Although potentially promising, such an oncogene was recently described by Sheng et al 7 Several drug modalities have been developed to target ErbB3; however, the utility of these modalities remains to be clinically established.…”
Section: Introductionmentioning
confidence: 99%